Motivated political reasoning: Testing the emotion regulation account in the case of perceptual divides over politically relevant facts. - Kiil, Filip (Politics & the Life Sciences)
Motivated political reasoning is a central phenomenon in political psychology, but no scholarly consensus exists as to its cause. In one influential account, motivated political reasoning is caused by goals to control emotional states. This explanation is often assumed, but has rarely been tested empirically. It implies, I argue, that individual differences in how people control their emotions (i.e., in emotion regulation strategies) should influence outcomes caused by motivated political reasoning, such as perceptual divides over politically relevant facts. I hypothesize such perceptual divides to be negatively associated with emotional acceptance and positively associated with cognitive reappraisal—two key emotion regulation strategies. I test these hypotheses in the specific context of reasoning about facts related to immigration politics in Denmark using a mix of experimental and cross-sectional survey data from three nationally representative samples of the Danish voter population (total N  = 4186). In the specific context of the present study, the results do not support the often-assumed idea that motivated political reasoning is driven by efforts to regulate emotions. These findings raise important questions about the conditions under which emotion regulation might play a role in motivated political reasoning.